2018
DOI: 10.3928/1081597x-20171214-01
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Apical Scar After Hyperopic Excimer Laser Refractive Surgery: Long-term Follow-up of Treatment With Sequential Customized Therapeutic Keratectomy

Abstract: Long-term results demonstrate that SCTK can treat this sight-threatening complication of hyperopic excimer laser refractive surgery, achieving significant improvements in visual acuity and in many corneal morphological parameters. [J Refract Surg. 2018;34(2):113-120.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The SCTK technique features a multi-step procedure and intraoperative monitoring. [10][11][12] SCTK was performed with the Nidek EC-5000 excimer laser between 2001 and February 2013. All surgical procedures required more than one phase on the same day, as described below.…”
Section: Sctk For Reis-bücklers' Corneal Dystrophymentioning
confidence: 99%
See 4 more Smart Citations
“…The SCTK technique features a multi-step procedure and intraoperative monitoring. [10][11][12] SCTK was performed with the Nidek EC-5000 excimer laser between 2001 and February 2013. All surgical procedures required more than one phase on the same day, as described below.…”
Section: Sctk For Reis-bücklers' Corneal Dystrophymentioning
confidence: 99%
“…Key to this approach was intraoperative topography, a powerful and accurate method to assess the preoperative and intraoperative corneal irregularities and elaborate, when necessary in sequential, repeated steps, a topography-guided ablation aimed at regularizing corneal surface. [10][11][12] A key tool in our surgical treatment of Reis-Bücklers' corneal dystrophy was smoothing with masking fluid. Since 1998, we have demonstrated that phototherapeutic-like smoothing improved corneal stromal surface regularity immediately after PRK and provided better refractive and optical outcomes.…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations